Study of the effect of ion nitriding regimes on the structure and hardness of steel - Sobol, Oleg; Andreev, Anatoly; Stolbovoy, Vyacheslav; Knyazev, Sergey; Barmin, Alexander; Krivobok, Natalya (Eastern-European Journal of Enterprise Technologies, 2016)
Application of low-temperature plasma nitriding of non-self-sustained arc low-pressure discharge allows solving a critical problem of increasing the stainless steel hardness and getting a wide range of structural states, including metastable at low temperatures, such as the S-phase (nitrided austenite). Using ion nitriding at a pressure of PN=(4…40)·10-4 Torr and constant negative potentials –600, –900 and –1300 V, the possibilities of structural engineering in the ion-induced surface modification and its influence on hardness are examined. When using ion nitriding regimes, the S-phase formation at the lowest pressure is revealed, the grating spacing of 0.381 nm is determined, which corresponds to the formula FeN0,4, and a large width of the diffraction reflections of the S-phase evidences fragmentation and high microstrain of the initial austenite in the S-phase formation. It is shown that the highest hardness can be obtained when the composition of CrN, S and the original austenitic phase is formed in the nitriding process, which is achieved under the following nitriding regimes: the pressure of 4·10-3 Torr and relatively low negative bias potential of 600 V.